2022
DOI: 10.4103/jmau.jmau_91_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological and morphometric study between medial and lateral menisci in aged male and female human cadavers

Abstract: Background: The meniscal cartilages are fibrous discs that are important for knee structures and have the ability to bear weight and stabilize joints. However, morphological and standard data for the meniscus are limited. Therefore, this work will compare anatomical and histological parameters of meniscal cartilages. The results will be important for the different measurements that are necessary for knee joint surgery. Materials and Methods: A total of 24 aged cadavers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Nevertheless, the etiology and implications for this sex difference remained unclear (Zhou et al, 2018;Pringle et al, 2019). In our previous study (Aggad et al, 2022), we found several differences of morphological and morphometric parameters of the MMi and LMi between males and females, which supported this gender-specific differences. Also, it was assumed that the alteration in cartilage composition, acting together with different walking mechanics between men and women, can potentially predispose women to a greater risk of OA (Blagojevic et al, 2010;Wise et al, 2012;Litwic et al, 2013;Kumar et al, 2015;Battistelli et al, 2019;Peshkova et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, the etiology and implications for this sex difference remained unclear (Zhou et al, 2018;Pringle et al, 2019). In our previous study (Aggad et al, 2022), we found several differences of morphological and morphometric parameters of the MMi and LMi between males and females, which supported this gender-specific differences. Also, it was assumed that the alteration in cartilage composition, acting together with different walking mechanics between men and women, can potentially predispose women to a greater risk of OA (Blagojevic et al, 2010;Wise et al, 2012;Litwic et al, 2013;Kumar et al, 2015;Battistelli et al, 2019;Peshkova et al, 2022).…”
Section: Discussionsupporting
confidence: 78%